The influence of temperatures, polarity, modifier and pressure to retention index in supercritical fluid chromatography: A review. Issue 1 (February 2021) - Idroes, R; Muslem; Mahmudi; Saiful; Paristiowati, M; Idroes, G M; Suhendra, R; Maulana, A; Noviandy, T R; Irvanizam
Abstract: Changes in analysis parameters affect the retention index calculation on all chromatography systems. In Supercritical Fluid Chromatography, the analysis parameters are more than Gas Chromatography or Liquid Chromatography. In this study, the effect of all those parameters were presented based on the research that has developed to date. The data and the information were collected from the previous published articles. The changes in the analysis parameters which are temperature, polarity, modifier, and pressure on SFC affected the retention index calculation, but the significant levels were different. The pressure change has the least significant effect for both polar and non-polar analytes. The temperature and stationary phase polarity changes have insignificant effects for non-polar analyte, but significant for polar one. Meanwhile, the modifier change have a very significant effect, both for polar and non-polar analytes.